2001
DOI: 10.1177/009365001028005003
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Message Valence and Listener Arousal on Attention, Memory, and Facial Muscular Responses to Radio Advertisements

Abstract: This study tested the validity of using facial electromyography (EMG) as a physiological measure of the valence of radio listeners' emotional responses toThe media expose audiences to a wide range of emotional experiences. Media messages contain content explicitly designed to evoke discrete emotions such as fear, anger, joy, and sadness. Producers are aware of the intimate relationship emotion has with three primary goals of media messages: to attract attention, to entertain, and to persuade. Given the prevale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
195
0
12

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 310 publications
(219 citation statements)
references
References 29 publications
12
195
0
12
Order By: Relevance
“…When average arousal figures were presented above it was seen that the average level of arousal for conflicted regions (the Eastern Anatolia: 42,60 and the South-eastern Anatolia:42.89) is much lower than the average level of arousal for the non-conflicted regions (the Aegean: 47,64 and the Mediterranean: 49,73). It was stated above that this finding was in line with a number of studies such as Jong-Meyer, 1990 andSimons et al, 1999;Reeves, Lang, Kim, & Tatar, 1999;Lang et al, 1999 andBolls et al, 2001). BERJ (8) 3 2017 The Pearson correlation analysis shows that there was a significant correlation between the level of pleasantness and purchase intention and moderate level of correlation with interest (r=-,56, p<0,01, r 2 =0,31) and arousal (r=,67, p<0,01, r 2 =0,45).…”
Section: Figure 2 Number Of Eye Fixationssupporting
confidence: 88%
See 1 more Smart Citation
“…When average arousal figures were presented above it was seen that the average level of arousal for conflicted regions (the Eastern Anatolia: 42,60 and the South-eastern Anatolia:42.89) is much lower than the average level of arousal for the non-conflicted regions (the Aegean: 47,64 and the Mediterranean: 49,73). It was stated above that this finding was in line with a number of studies such as Jong-Meyer, 1990 andSimons et al, 1999;Reeves, Lang, Kim, & Tatar, 1999;Lang et al, 1999 andBolls et al, 2001). BERJ (8) 3 2017 The Pearson correlation analysis shows that there was a significant correlation between the level of pleasantness and purchase intention and moderate level of correlation with interest (r=-,56, p<0,01, r 2 =0,31) and arousal (r=,67, p<0,01, r 2 =0,45).…”
Section: Figure 2 Number Of Eye Fixationssupporting
confidence: 88%
“…According to the test results there were no significant differences in the scores for arousal prior to the period of the Eastern Anatolia region package holiday advertisement is shown (M=40,11, SD= 11,88) and the Eastern Anatolia region package holiday advertisement is shown (M=42,60, SD= 11,83); t(20)= -,630, p= ,54, the period prior to the Aegean region package holiday advertisement is shown (M=50,30,SD= 17,45) and the period the Aegean region package holiday advertisement is shown (M=47,64, SD= 11,05); t(20)= ,782, p= ,443, the period prior to the South-Eastern Anatolia region package holiday advertisement is shown (M= 43,68,SD= 12,69) and the period the South-eastern Anatolia region package holiday advertisement is shown (M=42,89, SD= 14,65); t(20)= ,264, p= ,794 and the period of the Mediterranean region advertisement is shown (M= 55,12,SD= 17,76) This finding is in line with the findings of a number of studies which found that changes in experienced joyfulness resulted in higher levels of arousal (Jong-Meyer, 1990 andSimons et al, 1999;Reeves, Lang, Kim, & Tatar, 1999;Lang et al, 1999 andBolls et al, 2001). …”
Section: Findings and Analysissupporting
confidence: 87%
“…The benefits of EMG compared to coding from a video are the automation, objectivity (no observer biases), temporal precision (milliseconds), and detection of even minuscule responses [5]. On the other hand, facial EMG measurements are sensitive to noise, both of technical origin (e.g., bad contact between electrode and skin) and from confounding sources of muscle activity, such as speaking and other social communication (see behavioral ecology view [17]).…”
Section: Valence and Arousalmentioning
confidence: 99%
“…Lykken & Venables (1971) likened SCRs and the overall SCL to the waves on an ocean being responsible for the overall tidal drifts. They are both accepted as indications of the activation of the autonomic nervous system (Hopkins & Fletcher, 1993) and have been used as operational definitions in a variety of media-related experiments Bolls et al, 2001;Detenber, Simmons, & Bennet, 1998). Skin conductance data were collected using a Coulbourn S71-22 skin conductance coupler.…”
Section: Music Effects On Arousal -13mentioning
confidence: 99%